Work-related stress in the banking sector: a study on an Italian aged population of over 2,000 workers - Giorgi, Gabriele; Ariza Montes, Antonio; Rapisarda, Venerando; Campagna, Marcello; Garzaro, Giacomo; Arcangeli, Giulio; Mucci, Nicola (La Medicina del Lavoro, 2019)
Introduction: In the European Union, the employment rate for the population in the age group 55-64 years has greatly increased in the last two decades. Companies, especially in sectors such as banking, are looking for new strategies to improve the productivity of workers in this age group. Objectives: This study was conceived with the purpose of exploring the associations between job characteristics that could influence stress and certain organizational aspects in a large population of banking workers. Methods: More than 2,000 workers over 50 years of age of an Italian banking group participated in the study. Work-related stress was measured with the Stress Questionnaire (SQ). Organizational aspects of work were measured with a dedicated scale included in the SQ. Demographic aspects were detected by specific questions. Structural equation modelling was used and correlation coefficients were calculated. Results: The results from the structural equation modeling supported the theoretical model. Organizational policies are associated with both stress correlated factors (β=0.468) and perceptions of supervisor support and social support (β=0.710). The perception of both parameters is associated with stress outcomes (β=0.365). The proposed model offered better results than a competitive model, on which a total mediation was tested, rather than a partial one (p